The University of Illinois at Chicago School of Public Health Doctor of Public Health Program: An Innovative Approach to Doctoral-Level Practice Leadership Development - Lenihan, Patrick (Am J Public Health, 2015)
The University of Illinois at Chicago, School of Public Health, Doctor of Public Health degree is designed to build leadership skills and an ability to contribute to the evidence base of practice. The competency-based, distance-format, doctoral-level program for midcareer professionals features an action learning approach in which students apply leadership principles from the virtual classroom to real-world problems at their work sites. Students demonstrate mastery of the competencies and readiness to advance to the dissertation stage through completing a portfolio by using a process of systematic reflection. The practice-oriented dissertation demonstrates the ability to contribute to the evidence base of public health practice in an area of emphasis. Preliminary evaluation data indicate that the program is meeting its intended purposes.